(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 20:22:18
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)
bggg
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
求助得到的回答
b²=1
所以c²=a²+b²=a²+1
a²=c²-1
准线x=±a²/c
所以a²/c=3/2
2a²=3c
所以2c²-2=3c
2c²-3c-2=0
c>0
所以c=2
a²=3
a=√3
所以e=c/a=2√3/3
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)
=a^6-a^5b+a^5b-a^4b^2+a^4b^2-a^3b^3+a^3b^3-a^2b^4+a^2b^4-ab^5+ab^5-b^6
=a^6-b^6
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
化简【3A方-(A+B)(B-A)】【4(-B-A)(B-A)+5B方】
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
(3a-6b)/(a+b) - (5a-6b)/(a-b) - (4a-5b)/(a+b) - (7a-8b)/(a-b) 快
(3a-6b/a+b)-(5a-6b/a-b)-(4a-5b/a+b)-(7a-8b/b-a)
a+a-a+2a-3a-2b+3b-5b+3b-4b-5b
计算:3a+4b/a-b+3b/b-a-4a/a-b
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
已知A=5a-3b,B=-6a+4b,A-B=?
[(a+b)^-3(a-b)^5/(a-b)^-2(a+b)^4]^2怎么写
5(a-b)-4(a+b)-3(a-b)+2(a+b)怎么算?
(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?
计算:(a+2b)_2(a+2b)+3(a+2b)-4(a+2b)+5(a+2b)-.+99(a+2b)_100(a+2b)
计算:(a+2b)_2(a+2b)+3(a+2b)-4(a+2b)+5(a+2b)-.+99(a+2b)_100(a+2b)
把下列式子化成(a+b)^n或(a-b)^n的形式1.(a+b)^2*(b+a)^3+(a+b)^52.(a-b)^3*(a-b)^2-(a-b)^4*(a-b)+(a-b)^5
(a+b).(a-b)
a/b-b/a
a+b>a-b,